Results (displaying matches 1-50 of 234) Next

Label Class Equation Sato-Tate $$\overline{\Q}$$-simple $$\GL_2$$ Rank*
6982.a.13964.1 6982.a $$y^2 + (x^3 + 1)y = x^5 - 3x^3 + 2x$$ $\mathrm{USp}(4)$ 2
9055.a.45275.1 9055.a $$y^2 + y = x^5 + 3x^4 - 3x^2 - x$$ $\mathrm{USp}(4)$ 2
9278.a.18556.1 9278.a $$y^2 + (x^2 + x + 1)y = 2x^5 + 3x^4 - x^2$$ $\mathrm{USp}(4)$ 2
9633.a.28899.1 9633.a $$y^2 + x^3y = -2x^4 + 5x^2 - x - 2$$ $\mathrm{USp}(4)$ 2
9783.a.29349.1 9783.a $$y^2 + y = x^5 - 2x^3 + x^2$$ $\mathrm{USp}(4)$ 2
10762.a.21524.1 10762.a $$y^2 + (x^3 + 1)y = x^5 - x^4 - 3x^3 + x^2 + x$$ $\mathrm{USp}(4)$ 2
11944.c.382208.1 11944.c $$y^2 + y = 4x^5 - 7x^4 + 3x^3 + x^2 - x$$ $\mathrm{USp}(4)$ 2
12010.a.24020.1 12010.a $$y^2 + (x + 1)y = x^5 - 3x^4 + 5x^2 - 3x$$ $\mathrm{USp}(4)$ 2
12050.a.24100.1 12050.a $$y^2 + xy = x^5 - 2x^3 - x^2 + x + 1$$ $\mathrm{USp}(4)$ 2
12076.a.48304.1 12076.a $$y^2 + xy = x^6 - 3x^4 - x^3 + 2x^2 + x$$ $\mathrm{USp}(4)$ 2
12153.a.36459.1 12153.a $$y^2 + (x^3 + 1)y = x^5 - 5x^4 + 4x^3 - x$$ $\mathrm{USp}(4)$ 2
12275.a.61375.1 12275.a $$y^2 + (x^2 + x + 1)y = x^5 + 3x^4 + x^3 - x^2$$ $\mathrm{USp}(4)$ 2
12657.b.341739.1 12657.b $$y^2 + y = x^5 - x^4 + 2x^2 - 2x$$ $\mathrm{USp}(4)$ 2
12691.a.88837.1 12691.a $$y^2 + y = x^5 + 5x^4 + 5x^3 + x^2$$ $\mathrm{USp}(4)$ 2
13100.a.52400.1 13100.a $$y^2 + (x^2 + 1)y = x^5 + x^4 - 2x^3 - x^2 + x$$ $\mathrm{USp}(4)$ 2
13648.c.873472.1 13648.c $$y^2 + x^3y = -2x^4 - x^3 + 5x^2 + 8x + 4$$ $\mathrm{USp}(4)$ 2
13736.a.439552.1 13736.a $$y^2 + y = 4x^5 + 5x^4 - x^3 - 2x^2$$ $\mathrm{USp}(4)$ 2
13870.a.138700.1 13870.a $$y^2 + (x^3 + 1)y = x^5 + 2x^4 - 2x^2 - 2x$$ $\mathrm{USp}(4)$ 2
14050.a.140500.1 14050.a $$y^2 + (x + 1)y = x^6 - x^5 + 2x^4 + x^3 - 3x^2$$ $\mathrm{USp}(4)$ 2
14601.a.131409.1 14601.a $$y^2 + (x^3 + x^2 + x)y = 2x^4 + x^3 - 2x^2 - x$$ $\mathrm{USp}(4)$ 2
15380.a.307600.1 15380.a $$y^2 + xy = x^6 - 2x^5 + 2x^4 - 2x^3 + x$$ $\mathrm{USp}(4)$ 2
15681.a.47043.1 15681.a $$y^2 + y = x^5 - 2x^4 - x^3 + 3x^2 - x$$ $\mathrm{USp}(4)$ 2
15957.c.143613.1 15957.c $$y^2 + (x^3 + 1)y = -2x^4 + 9x^2 + 9x + 2$$ $\mathrm{USp}(4)$ 2
16130.a.161300.1 16130.a $$y^2 + (x^3 + x)y = -2x^4 - x^3 + 5x^2 - 2x$$ $\mathrm{USp}(4)$ 2
16737.a.351477.1 16737.a $$y^2 + y = x^5 + 4x^4 + 2x^3 - x$$ $\mathrm{USp}(4)$ 2
16978.a.33956.1 16978.a $$y^2 + (x^3 + 1)y = -2x^4 + 2x^2 - x$$ $\mathrm{USp}(4)$ 2
17031.a.51093.1 17031.a $$y^2 + (x^2 + x + 1)y = x^5 - 2x^3 + x$$ $\mathrm{USp}(4)$ 2
17194.a.550208.1 17194.a $$y^2 + xy = x^5 + 3x^4 - 4x^2 - x + 1$$ $\mathrm{USp}(4)$ 2
17768.a.568576.1 17768.a $$y^2 + x^3y = x^5 + x^4 - x^3 - x^2 + 4x + 4$$ $\mathrm{USp}(4)$ 2
17984.b.143872.1 17984.b $$y^2 + xy = x^6 - 2x^5 - 2x^4 + 3x^3 + x^2 - x$$ $\mathrm{USp}(4)$ 2
18344.b.587008.1 18344.b $$y^2 + (x^3 + x^2 + x + 1)y = -x^4 - 5x^3 + x^2 + x$$ $\mathrm{USp}(4)$ 2
19905.a.179145.1 19905.a $$y^2 + (x^2 + x + 1)y = x^5 - x^4 - 5x^3 + 2x^2 + 3x$$ $\mathrm{USp}(4)$ 2
20072.b.642304.1 20072.b $$y^2 + (x^3 + x)y = x^3 + 3x^2 - x$$ $\mathrm{USp}(4)$ 2
20331.b.182979.1 20331.b $$y^2 + y = x^5 + 2x^4 - x^3 - x^2 + x$$ $\mathrm{USp}(4)$ 2
21058.a.673856.1 21058.a $$y^2 + (x + 1)y = x^5 + x^4 - 3x^3 + x^2$$ $\mathrm{USp}(4)$ 2
21303.b.575181.1 21303.b $$y^2 + (x^3 + x^2 + x + 1)y = -x^4 - 5x + 2$$ $\mathrm{USp}(4)$ 2
21784.a.174272.1 21784.a $$y^2 + (x^3 + x)y = -x^4 - 2x^3 + x^2 + 2x$$ $\mathrm{USp}(4)$ 2
22602.a.135612.1 22602.a $$y^2 + (x^3 + 1)y = x^5 + x^4 - 3x^3 - 5x^2 + x + 4$$ $\mathrm{USp}(4)$ 2
22630.a.226300.1 22630.a $$y^2 + (x^3 + 1)y = x^4 + 3x^3 - x^2 - 4x$$ $\mathrm{USp}(4)$ 2
23186.a.370976.1 23186.a $$y^2 + (x + 1)y = -x^5 + x^4 + x^3 + x^2 + x$$ $\mathrm{USp}(4)$ 2
23289.a.489069.1 23289.a $$y^2 + y = 3x^5 - 7x^4 + 6x^3 - 2x^2$$ $\mathrm{USp}(4)$ 2
23631.b.638037.1 23631.b $$y^2 + x^3y = x^5 - x^4 - 5x^3 + 5x + 2$$ $\mathrm{USp}(4)$ 2
23695.a.829325.1 23695.a $$y^2 + y = x^5 + 3x^4 + 3x^3 + 4x^2 + x$$ $\mathrm{USp}(4)$ 2
24064.b.96256.1 24064.b $$y^2 + (x + 1)y = x^6 - 2x^4 - x^3 + x^2$$ $\mathrm{USp}(4)$ 2
24296.a.777472.1 24296.a $$y^2 + (x^3 + x)y = 2x^4 - x^3 + x^2 + x$$ $\mathrm{USp}(4)$ 2
24320.b.243200.1 24320.b $$y^2 + y = 2x^5 + 3x^4 + x^3$$ $\mathrm{USp}(4)$ 2
24340.a.97360.1 24340.a $$y^2 + xy = x^6 + x^4 - 5x^3 + 4x^2 - x$$ $\mathrm{USp}(4)$ 2
25280.a.505600.1 25280.a $$y^2 + (x^3 + x)y = -2x^4 - x^3 - x^2 - x + 1$$ $\mathrm{USp}(4)$ 2
25570.b.255700.1 25570.b $$y^2 + (x^3 + 1)y = x^5 - x^4 - 5x^3 + 4x^2 + 4x - 3$$ $\mathrm{USp}(4)$ 2
26145.a.392175.1 26145.a $$y^2 + (x^3 + 1)y = x^5 - x^4 + 4x^2 + 2x$$ $\mathrm{USp}(4)$ 2
Next